Illegal construction in the languaqe sphere - Rakić, Branko (Sociološki pregled, 2021)
Stating that social action aimed at achieving a higher degree of equality between men and women is necessary and useful, the author questions the validity of the approach in the recently adopted Law on Gender Equality that tries to establish gender equality, among other things, by forced intervention in the language sphere, through imposing the application of the so-called “gender-sensitive language”. Despite the fact that such an approach could hardly contribute to actual equality, this forced intervention in the language sphere is the violation of the language as a segment of intangible cultural heritage, which is contrary to the Constitution of the Republic of Serbia and a number of international acts. Fortunately, the provisions of the Law on Gender Equality regarding the application of gender-sensitive language are inaccurate, unclear and full of internal contradictions to such an extent that it can be said that they are not applicable.